Factors Affecting Micro and Small-Scale Industries Income: A Case Study on Coffee Processing Industry - Lya Aklimawati; Djoko Soemarno; Surip Mawardi (Indonesian Coffee and Cocoa Research Institute, 2016)
Development the competitive industries primarily small firms ought to be realized for improving economic growth of a community. Small industries have an important role especially on income equity improvement in rural areas. The objective of this study was to assess industry players motivation for developing their business in coffee processing and also to analyze factors which influence business income focused on micro and small-scale coffee industries in Bondowoso District. Survey method was used in this study for collecting primary and secondary data. A number of respondents were 25 coffee industry players who be determined by judgement sampling method. Data were analyzed by descriptive and statistic method. Multiple linear regression was used in the suspected factors that affect small industries income. The results indicated that the main motivation of industry players in initiating and developing coffee business was financial incentive. Consecutively, indicators that may explain industry player’s motivation were expectation, motive and incentive. Micro and small-scale industries income was affected by raw material, marketing reach, technology and business experience. Meanwhile, micro and small-scale industries income was not affected by labor cost and source of capital.